2011
DOI: 10.1017/s0022215111001435
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative nausea and vomiting following paediatric day-case tonsillectomy: audit of the Epsom protocol

Abstract: These findings have implications for the safe same-day discharge of children following tonsillectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…This is similar to the literature, in which about 1.3% of patients experience delayed discharge during the initial hospital stay, and up to 3.9% have secondary complications requiring admission 8 . The incidence of non-respiratory complications (dehydration 4.5%, hemorrhage 2.3% and fever 0.5%) was also similar to that reported from other studies 25 . However, the rate of post-operative respiratory complications was lower (1.4%) than the range of 5–23% reported in the literature 26–28 .…”
Section: Discussionsupporting
confidence: 89%
“…This is similar to the literature, in which about 1.3% of patients experience delayed discharge during the initial hospital stay, and up to 3.9% have secondary complications requiring admission 8 . The incidence of non-respiratory complications (dehydration 4.5%, hemorrhage 2.3% and fever 0.5%) was also similar to that reported from other studies 25 . However, the rate of post-operative respiratory complications was lower (1.4%) than the range of 5–23% reported in the literature 26–28 .…”
Section: Discussionsupporting
confidence: 89%
“…Postoperative nausea and vomiting after tonsillectomy is a complication that, along with postoperative pain, can significantly compromise the patient's quality of life. Many studies have shown that drugs such as ondansetron, palonosetron, metoclopramide, dexamethasone, and midazolam can reduce PONV . However, the exact mechanism of action of midazolam and dexamethasone is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found no significant association between PSG parameters and nonrespiratory complications, and the incidence of nonrespiratory complications was similar to those from other studies. 8,9,29 …”
Section: Discussionmentioning
confidence: 99%